(untitled) (Studia austriaca, 2016)
Gerhard Fritsch’s early novel Moos auf den Steinen (1956) represents a turning point in post-WWII Austrian literature. As other authors did just after the fall of the Habsburg Monarchy, Fritsch outlines the new reality and the legacy his generation inherited from a dissolving past. This essay focuses on the relevance of past memory in Moos auf den Steinen and on the way each character deals with it. Moreover, since Fritsch’s production represents a significant contribution to the poetics of Thomas Bernhard, the last chapter focuses entirely on their personal and professional relationship.